CONTRIBUTION OF SCHOOL PRINCIPAL LEADERSHIP AND TEACHER PERFORMANCE TOWARDS ACADEMIC ACHIEVEMENT OF MI STUDENTS IN TABANAN DISTRICT - Rosyana Ulfah (JOURNAL OF HUMANITIES AND SOCIAL STUDIES, 2024)
This research can be used as material to expand and deepen the theory of principal leadership and teacher performance on student academic achievement results. The subjects of this research were all MI teachers in Tabanan Regency, totaling 114 teachers, with a sample of 89 people and using proportional stratified random sampling techniques. The method used for data collection is the questionnaire method. The data analysis used is descriptive analysis, prerequisite tests and hypothesis testing which includes multiple linear regression analysis to determine the effect of teacher working group activities and academic supervision on teacher performance. Data analysis used the SPSS 21 for Windows program. The results of the research show that the leadership of the school principal has a positive and significant effect on the academic achievement results of MI students in Tabanan Regency with p = 0.012. The more the principal's leadership increases, the more students' academic achievements will increase. Teacher performance has a positive and significant effect on the academic achievement results of MI students in Tabanan Regency with p = 0.000. The better the teacher's performance, the higher the student learning achievement results will be. with p = 0.000. The more the principal's leadership and teacher performance improve, the student learning achievement results will also increase. By looking at the results of this research, it is hoped that it can be used as study material for the scope of relevant problems in the world of education.